Comparison Techniques for Optimization Switching Frequency in Energy Encryption of Wireless Power Transfer System - Nur Hazwani Hussin; Azuwa Ali; Muhammad Mokhzaini Azizan; Ir. Ts. Dr. Norhidayu Rameli; Nur Hazirah Zaini; Shahnurriman Abdul Rahman (Semarak Ilmu Publishing, 2024)
Indexed by Scopus/MyCite